Teilhard de Chardin and the Present Dialogue between Science and Religion - Udías Vallina, Agustín (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
We can find in Teilhard’s writings many points of interest for the dialogue between science and religion. I have selected three of them: his understanding of science, matter and human evolution. The first is his high esteem for science and its role in human history. Science for him represents the line along which evolution progresses towards the human level. Science goes beyond its specific function and also prepares people to find the profound and hidden meaning of reality. This understanding of science may serve as a good starting point in the science-religion dialogue, since it recognizes a potentiality in science to be interpreted in religious terms. The second is his understanding of matter which surpasses all matter-spirit dualism. Matter for him has an internal dynamism, which leads it to the spirit, through the process of cosmic evolution. The third is his conception of human evolution as part of cosmic evolution. By this, the consciousness of man (noosphere), progresses along the line of increasing unity to finally converge into an Omega Point, where it finds its ultimate fulfillment.